(untitled) (International Journal of Environmental Sciences, 2025)
Using cutting-edge data analytics methods, this research delves at how consumers of all generations buy gender-neutral personal care items. Knowing the subtleties of how different age groups react to these trends is critical for marketers and product developers, especially with the increasing focus on inclusion and gender neutrality in consumer goods. This study looks at the buying habits, tastes, and perspectives of Millennials, Gen Xers, and Baby Boomers using a large dataset and statistical and machine learning techniques. There are clear disparities in product choices, buying motivations, and brand views between generations, according to the data. While members of Generation X and Baby Boomers are more likely to buy items based on their practicality and brand loyalty, Millennials are more likely to purchase gender-neutral products because they emphasise equality and sustainability. The study’s results may be used to create marketing strategies and products that are more relevant to today’s consumers and their changing preferences. This study adds to our knowledge of consumer behaviour across generations and shows how important it is to use data analytics to tackle market changes.